Effect of chain extender and terpolymers on tensile and fracture properties of polyamide 6. (18th May 2015) - Yilmaz, Sinan; Gul, Okan; Yilmaz, Taner
Abstract: This work was aimed at improving essential work of fracture (EWF) toughness of Polyamide 6 (PA6) without sacrificing the mechanical properties, whereby two different kinds of terpolymer were incorporated into the PA6 matrix. Furthermore, 1.1′-carbonyl-bis-caprolactam (CBC), as a chain extender, was added into PA6/Lotader blends to reveal the effect of chain entanglement on fracture behavior of the blends. Tensile test results indicated that incorporation of Lotader and CBC did not cause a significant reduction on mechanical properties of the blends, on the contrary caused an enhancement of yielding strength. It was observed that the incorporation of Lotader in to PA6 matrix gave rise to a remarkable enhancement on the EWF toughness especially in presence with CBC. Energy partitioning concept was also employed for further analysis and inference on the effect of additive type and ratio on fracture toughness of PA6 blends. Graphical abstract: Highlights: We incorporated two different kinds of terpolymer and chain extender into polyamide 6 by using melt extrusion method. In order to analysis fracture behavior and fracture toughness of the materials, we used essential work of fracture concept. Maximum fracture toughness value, almost two-fold higher than neat PA6, was obtained from PA6/Lotader 4700/CBC blends. Lotader and CBC slightly increased yielding strength of PA6 without a significant reduction on other mechanical properties. Thermal and morphological properties of the materials were also investigated properly.